Universities and economic development in Africa : Pact, academic core and Coordination. - Cloete, Nico; Bailey, Tracy (African MindsPUBLISHER, African Books Collective Limited [distributor], 2011)
Universities and economic development in Africa: Pact, academic core and coordination draws together evidence and synthesises the findings from eight African case studies. The three key findings presented in this report are as follows: 1. There is a lack of clarity and agreement (pact) about a development model and the role of higher education in development, at both national and institutional levels. There is, however, an increasing awareness, particularly at government level, of the importance of universities in the global context of the knowledge economy. 2. Research production at the eight.